(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The healthcare industry provides medical devices such as pharmaceuticals. The third-party vendor can also pose a risk to the organization. Cyber security if they are not properly vetted and do not have adequate security measures in place. These will help to mitigate and other cyber security risks, healthcare organizations should implement a range of security measures. Regular security assessments in healthcare organizations should conduct a regular security assessment to identify vulnerable in their systems and network. Distributed dental or services attacks where criminals overload the healthcare system. Health care system servers with traffic, causing them to crash and preventive. Lag mate users from accessing the system’s network, stealing data, and causing damage to the system. Ensure that these tools are updated regularly to protect against the latest threats. Regularly check the backup data and critical data and store them in a secure location. Monitoring network activity to detect and respond to any potential security incidents conduct regularly.